Assessment and Strengthening of Bolted Connections in the Mandomai Bowstring Bridge Constructed with Ulin Wood - Subchan, Shafira Khairunnisa; Awaludin, Ali; Akbar, Miqdad Khosyi; Tama, Radika Gandi; Setiawan, Angga Fajar; Yudhistira, Angga Trisna; Irawati, Inggar Septhia; Triwiyono, Andreas (Civil Engineering Dimension, 2026)
This study assessed and proposed a retrofit strategy for bolted timber connections in the Mandomai pedestrian bridge, constructed from Ulin wood (Eusideroxylon zwageri). Numerical modeling, analytical evaluation using Eurocode 5 yield equations, and experimental validation were conducted. Axial forces from a global Midas Civil model under a 1.25 kN/m² live load showed three critical connections (S11, S13, S14) with demand-capacity ratios (DCR) exceeding 1.0. A retrofit using steel side plates and ASTM A325 bolts reduced DCRs to 0.79, 1.02, and 0.70, respectively. Experimental testing of limited full-scale double-shear wood-to-wood joints demonstrated an average ultimate capacity of 191 kN, which was 57.65% higher than the theoretical prediction, indicating the conservative nature of Eurocode 5 and the contribution of mechanisms such as the rope effect and frictional interlock. The results confirmed the retrofit’s effectiveness and highlighted the need to refine design provisions for dense tropical hardwoods.